2007
DOI: 10.1051/alr:2007013
|View full text |Cite
|
Sign up to set email alerts
|

Parasite co-infection of two sympatric bivalves, the Manila clam (Ruditapes philippinarum) and the cockle (Cerastoderma edule) along a latitudinal gradient

Abstract: . Parasite coinfection of two sympatric bivalves, the Manila clam (Ruditapes philippinarum) and the cockle (Cerastoderma edule) along a latitudinal gradient. Aquatic Living Resources, EDP Sciences, 2007, 20, pp.33-42. <10.1051/alr:2007013>. Aquat. Living Resour. 20, 33-42 (2007 Abstract -Among the potential biotic factors affecting population dynamics, parasitism has received relatively little attention. The purpose of this study was to inventory marine bivalve parasites and to investigate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 39 publications
5
37
3
Order By: Relevance
“…The increasing north-south latitudinal gradient of Perkinsus sp. abundance reported by Lassalle et al (2007) confirmed that this protozoan prefers higher temperatures. Chu et al (1996) and Park & Choi (2001) reported that high water temperatures enhance infection intensity and prevalence of P. marinus.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The increasing north-south latitudinal gradient of Perkinsus sp. abundance reported by Lassalle et al (2007) confirmed that this protozoan prefers higher temperatures. Chu et al (1996) and Park & Choi (2001) reported that high water temperatures enhance infection intensity and prevalence of P. marinus.…”
Section: Discussionsupporting
confidence: 61%
“…In Europe, Perkinsus sp. was found in R. philippinarum in Spain (Navas et al 1992), Italy (Da Ros & Canzonier 1985, Da Ros et al 1998 and France (Lassalle et al 2007).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…R. decussatus from Arcachon Bay is colonized only with 4 species (Curtuteria arguinae, Himasthla sp., M. fossarum, unknown metacercariae). Compared to Ruditapes philippinarum from Arcachon Bay (Dang, 2009) and from the French Atlantic shore (Lassalle et al, 2007), R. decussatus from our coasts is elsewhere more infected; manila clams were respectively infected only by 3 species (Curtuteria arguinae and Himasthla continua, Psilostomum brevicole) and 5 species (Himasthla quissetensis, H. interrupta, H. elongate, Curtuteria arguinae, Psilostomum brevicolle). The digenean diversity of R. decussatus from Tunisian coasts, relatively more important, is undoubtedly related to the strategic situation of Tunisia, that representing a transition zone between the western and eastern Mediterranean, undergoes the infl uence of the Atlantic through the straits of Gibraltar and of the Red Sea via the Suez canal.…”
Section: Global Values Of Parasitical Indices Of Different Digenean Smentioning
confidence: 64%
“…Brown Muscle Disease (BMD) appeared as a prevalent pathology for Manila clams in Arcachon Bay where it can be considered as the second disease in term of prevalence, behind perkinsosis (Lassalle et al 2007), but before helminthosis (Dang et al Submitted) or brown ring disease (Lassalle et al 2007). BMD affected adult Manila clams only (>25 mm or >2 y).…”
Section: Discussionmentioning
confidence: 99%